Socio-Economic Environmental Feasibility of Groundwater Pricing in the UAE - ALYAMMAHI, SOMAYYAH ABDULLA (2023)
Environmental responsibility and preventing depletion are among the country's fundamental development principles. The UAE depends on its groundwater resources, particularly groundwater accounts for 93% of total agriculture water use. Farmers and landowners are free of charges for groundwater use, while power bills are subsidized. However, with their already limited availability, groundwater resources have been aggressively exploited to maintain farm productivity in the desert. This paper analyzes the most critical proposed scenarios for pricing groundwater in the UAE for groundwater. For the sustainability of a groundwater resource and to reduce the water demand in the agriculture sector. To respond to this issue, various investigative methodologies have been used to achieve the study objective, including descriptive, analytical, and deductive approaches, which are generated sequentially to select the best scenario of integration. The results and analyses showed that the best and appropriate method for pricing groundwater is a volumetric pricing tariff according to the quantity of extracted water since the contributes of the agriculture area is fewer than 1% to the UAE’s gross domestic product (GDP). In conclusion, the final groundwater tariff conducted and reflected, measured as an economic and environmental impact to reflect the results of this study with a proposed implementation plan if the government decides to execute it.